The Role of Verbal and Written Praise in Enhancing Speaking Skills: A Quantitative Study on third-Semester English Students at the Faculty of Education, University of Zawiya (Comprehensive Journal of Science, 2026)
Speaking skills are crucial for English as a  foreign Language (ESL) learners, yet many students face challenges such as anxiety and lack of confidence. This study investigates the role of verbal and written praise as positive reinforcement strategies to enhance speaking skills. Conducted among 50 third-semester English female students at the Faculty of Education, University of Zawiya, the research employs a structured questionnaire as t sole data collection tool. Results reveal that verbal praise significantly boosts students’ confidence during speaking tasks, while written praise helps them reflect on and track their progress. A combination of both strategies was most effective, with 60% of participants preferring this approach. The study concludes that integrating verbal and written praise into teaching methods can create a supportive environment that fosters speaking proficiency. The findings contribute to pedagogical practices and encourage further research on motivational strategies in ESL contexts.
Keywords: Praise, Verbal praise ,Written praise, Motivation , Supportive environment